S2k-guideline non-hormonal contraception, part 2: intrauterine devices and sterilization : guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry No. 015-095, January 2024) - Böttcher, Bettina; Beckermann, Maria J.; Berger, Barbara; Cremers, Jann-Frederik; D'Costa, Elisabeth; Frank-Herrmann, Petra; Freundl-Schuett, Tanja; Friedrich, Cornelia; Funck, Soeren; Gathmann, Christine; Goeckenjan, Maren; Goette, Sabine; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Aim This official guideline was published and coordinated by the DGGG, OEGGG and SGGG with the involvement of other medical societies. The aim was to provide a consensus-based overview of non-hormonal forms of contraception based on an evaluation of the relevant literature. The first part of these summarized statements and recommendations presents natural family planning methods such as lactational amenorrhea, barrier methods and coitus interruptus. The second part focuses on intrauterine devices and sterilization. Methods This S2k-guideline was developed by representative members from different medical professions on behalf of the guidelines commission of the DGGG, OEGGG and SGGG using a structured consensus process. Recommendations The guideline provides recommendations on the indications for, safety of use, benefits, and limitations of the different methods as well as recommendations on providing advice and other aspects of non-hormonal contraception. This summary presents recommendations and statements about intrauterine devices and female and male sterilization.
Online veröffentlicht am 6. August 2024
Gesehen am 03.06.2024